Acute respiratory failure after aspiration of activated charcoal with recurrent deposition and release from an intrapulmonary cavern - Francis, Roland C. E.; Schefold, Joerg C.; Bercker, Sven; Temmesfeld-Wollbrueck, Bettina; Weichert, Wilko; Spies, Claudia D.; Weber-Carstens, Steffen (Intensive Care Medicine, 2009)
Objective: To report on the recurrent release of charcoal from an intrapulmonary cavern in a case of acute respiratory failure after charcoal aspiration. Design: Case report. Setting: Anaesthesiological ICU, university hospital. Patient: An 18-year-old ethanol intoxicated comatose patient regurgitated and aspirated activated charcoal during orotracheal intubation. Treatment: After 2 days of mechanical ventilation, the patient was transferred to a tertiary care university hospital. On admission, acute respiratory distress syndrome with bilateral pulmonary infiltrations was diagnosed. The patient's recovery was hampered by recurrent release of charcoal from an intrapulmonary cavern. Sophisticated ventilatory support, prone positioning, secretolytics, repetitive bronchoscopy, and antibiotic therapy may have facilitated bronchoalveolar clearance and weaning after 18 days. Conclusion: Aspiration may be a dramatic complication if charcoal is administered in comatose patients without airway protection. In this case report, advanced intensive care measures were necessary to tackle the special feature of charcoal release from an intrapulmonary cavern. © 2008 Springer-Verlag.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Activated charcoal; Acute respiratory distress syndrome; Acute respiratory failure; Aspiration; Cavern

Adherence to guideline-based standard operating procedures in pre-hospital emergency patients with chronic obstructive pulmonary disease - Bosse, G.; Schmidbauer, W.; Spies, C. D.; Soerensen, M.; Francis, Roland C. E.; Bubser, F.; Krebs, M.; Kerner, T. (Journal of International Medical Research, 2011)
This study investigated improvements in pre-hospital care for patients with acute exacerbated chronic obstructive pulmonary disease (aeCOPD) achieved by using a standard operating procedure (SOP). An SOP for pre-hospital treatment of patients with aeCOPD was designed based on valid national guidelines. A total of 1000 Emergency Medical Service patient care reports were analysed prospectively: 500 before and 500 after introduction of the SOP. Overall guideline adherence was 34.6% before and 53.8% after introduction of the SOP; this increase was not statistically significant. After SOP introduction, the administration of b2- mimetics by inhalative, intravenous and subcutaneous routes increased significantly. The level of knowledge of the national guidelines was rated at 67% by emergency physicians during self- assessment, but was only 33% when physicians were asked specific questions during interview. Introducing the SOP for patients with aeCOPD did not significantly improve adherence to valid national guidelines, but did help to improve specific elements of therapy. © 2011 Field House Publishing LLP.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Chronic obstructive pulmonary disease (COPD); Guideline implementation; Standard operating procedures

Administration of hydrogen sulfide via extracorporeal membrane lung ventilation in sheep with partial cardiopulmonary bypass perfusion: A proof of concept study on metabolic and vasomotor effects - Derwall, Matthias; Francis, Roland C. E.; Kida, Kotaro; Bougaki, Masahiko; Crimi, Ettore; Adrie, Christophe; Zapol, Warren M.; Ichinose, Fumito (Critical Care, 2011)
Introduction: Although inhalation of 80 parts per million (ppm) of hydrogen sulfide (H2S) reduces metabolism in mice, doses higher than 200 ppm of H2S were required to depress metabolism in rats. We therefore hypothesized that higher concentrations of H2S are required to reduce metabolism in larger mammals and humans. To avoid the potential pulmonary toxicity of H2S inhalation at high concentrations, we investigated whether administering H2S via ventilation of an extracorporeal membrane lung (ECML) would provide means to manipulate the metabolic rate in sheep.Methods: A partial venoarterial cardiopulmonary bypass was established in anesthetized, ventilated (fraction of inspired oxygen = 0.5) sheep. The ECML was alternately ventilated with air or air containing 100, 200, or 300 ppm H2S for intervals of 1 hour. Metabolic rate was estimated on the basis of total CO2 production (V̇ CO2) and O2 consumption (V̇ O2). Continuous hemodynamic monitoring was performed via indwelling femoral and pulmonary artery catheters.Results: V̇ CO2, V̇ O2, and cardiac output ranged within normal physiological limits when the ECML was ventilated with air and did not change after administration of up to 300 ppm H2S. Administration of 100, 200 and 300 ppm H2S increased pulmonary vascular resistance by 46, 52 and 141 dyn·s/cm5, respectively (all P ≤ 0.05 for air vs. 100, 200 and 300 ppm H2S, respectively), and mean pulmonary artery pressure by 4 mmHg (P ≤ 0.05), 3 mmHg (n.s.) and 11 mmHg (P ≤ 0.05), respectively, without changing pulmonary capillary wedge pressure or cardiac output. Exposure to 300 ppm H2S decreased systemic vascular resistance from 1,561 ± 553 to 870 ± 138 dyn·s/cm5 (P ≤ 0.05) and mean arterial pressure from 121 ± 15 mmHg to 66 ± 11 mmHg (P ≤ 0.05). In addition, exposure to 300 ppm H2S impaired arterial oxygenation (PaO2 114 ± 36 mmHg with air vs. 83 ± 23 mmHg with H2S; P ≤ 0.05).Conclusions: Administration of up to 300 ppm H2S via ventilation of an extracorporeal membrane lung does not reduce V̇ CO2 and V̇ O2, but causes dose-dependent pulmonary vasoconstriction and systemic vasodilation. These results suggest that administration of high concentrations of H2S in venoarterial cardiopulmonary bypass circulation does not reduce metabolism in anesthetized sheep but confers systemic and pulmonary vasomotor effects. © 2011 Derwall et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2022-11-17

Age of red cells for transfusion and outcomes in patients with ARDS - Graw, Jan A.; Buenger, Victoria; Materne, Lorenz A.; Krannich, Alexander; Balzer, Felix; Francis, Roland C. E.; Pruss, Axel; Spies, Claudia D.; Kuebler, Wolfgang M.; Weber-Carstens, Steffen; Menk, Mario; Hunsicker, Oliver (Journal of Clinical Medicine, 2022)
Packed red blood cells (PRBCs), stored for prolonged intervals, might contribute to adverse clinical outcomes in critically ill patients. In this study, short-term outcome after transfusion of PRBCs of two storage duration periods was analyzed in patients with Acute Respiratory Distress Syndrome (ARDS). Patients who received transfusions of PRBCs were identified from a cohort of 1044 ARDS patients. Patients were grouped according to the mean storage age of all transfused units. Patients transfused with PRBCs of a mean storage age ≤ 28 days were compared to patients transfused with PRBCs of a mean storage age > 28 days. The primary endpoint was 28-day mortality. Secondary endpoints included failure-free days composites. Two hundred and eighty-three patients were eligible for analysis. Patients in the short-term storage group had similar baseline characteristics and received a similar amount of PRBC units compared with patients in the long-term storage group (five units (IQR, 3-10) vs. four units (2-8), p = 0.14). The mean storage age in the short-term storage group was 20 (±5.4) days compared with 32 (±3.1) days in the long-term storage group (mean difference 12 days (95%-CI, 11-13)). There was no difference in 28-day mortality between the short-term storage group compared with the long-term storage group (hazard ratio, 1.36 (95%-CI, 0.84-2.21), p = 0.21). While there were no differences in ventilator-free, sedation-free, and vasopressor-free days composites, patients in the long-term storage group compared with patients in the short-term storage group had a 75% lower chance for successful weaning from renal replacement therapy (RRT) within 28 days after ARDS onset (subdistribution hazard ratio, 0.24 (95%-CI, 0.1-0.55), p < 0.001). Further analysis indicated that even a single PRBC unit stored for more than 28 days decreased the chance for successful weaning from RRT. Prolonged storage of PRBCs was not associated with a higher mortality in adults with ARDS. However, transfusion of long-term stored PRBCs was associated with prolonged dependence of RRT in critically ill patients with an ARDS.
CRIS-Team Scopus Importer:2022-11-17
Keywords: ARDS; Red blood cells; Transfusion

Aortic volume determines global end-diastolic volume measured by transpulmonary thermodilution - Akohov, Aleksej; Barrier, Christoph; Grimmer, Steffen; Francis, Roland C. E.; Wolre, Stefan (Intensive Care Medicine Experimental, 2020)
Background: Global end-diastolic volume (GEDV) measured by transpulmonary thermodilution is regarded as indicator of cardiac preload. A bolus of cold saline injected in a central vein travels through the heart and lung, but also the aorta until detection in a femoral artery. While it is well accepted that injection in the inferior vena cava results in higher values, the impact of the aortic volume on GEDV is unknown. In this study, we hypothesized that a larger aortic volume directly translates to a numerically higher GEDV measurement. Methods: We retrospectively analyzed data from 88 critically ill patients with thermodilution monitoring and who did require a contrast-enhanced thoraco-abdominal computed tomography scan. Aortic volumes derived from imaging were compared with GEDV measurements in temporal proximity. Results: Median aortic volume was 194 ml (interquartile range 147 to 249 ml). Per milliliter increase of the aortic volume, we found a GEDV increase by 3.0 ml (95% CI 2.0 to 4.1 ml, p < 0.001). In case a femoral central venous line was used for saline bolus injection, GEDV raised additionally by 2.1 ml (95% CI 0.5 to 3.7 ml, p = 0.01) per ml volume of the vena cava inferior. Aortic volume explained 59.3% of the variance of thermodilution-derived GEDV. When aortic volume was included in multivariate regression, GEDV variance was unaffected by sex, age, body height, and weight. Conclusions: Our results suggest that the aortic volume is a substantial confounding variable for GEDV measurements performed with transpulmonary thermodilution. As the aorta is anatomically located after the heart, GEDV should not be considered to reflect cardiac preload. Guiding volume management by raw or indexed reference ranges of GEDV may be misleading.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Aorta; Aortic volume; GEDV; GEDVI; Global end-diastolic volume; Transpulmonary thermodilution; Vena cava; Vena cava volume

Arterial pulse-contour analysis Arterielle pulskonturanalyse - Francis, Roland C. E. (Journal für Anasthesie und Intensivbehandlung, 2012)
CRIS-Team Scopus Importer:2022-11-17

Assessment of hemodynamic efficacy and safety of 6% hydroxyethyl starch 130/0.4 vs. 0.9% NaCl fluid replacement in patients with severe sepsis: how to guide fluid therapy? - Hunsicker, Oliver; Francis, Roland C. E. (Critical Care, 2012)
CRIS-Team Scopus Importer:2022-11-17

Atemwegsmanagement in der Kinderanästhesie: Anwendung von Materialien und Methoden - Krebs, Martin; Mueller-Lobeck, Lutz; Francis, Roland C. E. (AINS - Anästhesiologie. Intensivmedizin. Notfallmedizin. Schmerztherapie., 2018)
CRIS-Team Scopus Importer:2022-11-17

Automated positive end-expiratory pressure titration during mechanical ventilation - Von Platen, Philip; Pomprapa, Anake; Lohse, Arnhold; Leonhardt, Steffen; Pickerodt, Philipp A.; Russ, Martin; Taher, Mahdi; Boerger, Emilia; Francis, Roland C. E.; Walter, Marian (IFAC-PapersOnLine, 2021)
Optimizing the positive end-expiratory pressure remains challenging for any clinician treating a patient with acute respiratory distress syndrome. This paper presents an approach to automate a PEEP titration maneuver and identify the best PEEP according to maximal compliance. The respiratory system was modeled by a single-compartment model, and parameters were estimated using multiple linear regression. A classifier identified the best PEEP using the scaled relative change in compliance between PEEP levels based on empirical data from previous manual PEEP titrations. An experimental system allows the in vivo testing of the automated PEEP titration, including additional safety measures. The complete system was tested in a single animal experiment and correctly identified the best PEEP. The introduced system is a step closer towards an automated, standardized PEEP optimization and closed-loop control of mechanical ventilation.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Artificial intelligence; Critical care; Decision support systems; Feedback control; Mechanical ventilation

Automatic artificial ventilation therapy using the ARDSNet protocol enforcing dynamical constraints - Pomprapa, Anake; Pickerodt, Philipp A.; Braun, Wolfgang; Russ, Martin; Hofferberth, Moritz B.T.; Walter, Marian; Misgeld, Berno; Francis, Roland C. E.; Lachmann, Burkhard; Leonhardt, Steffen (2017 25th Mediterranean Conference on Control and Automation, MED 2017, 2017)
In this work, a medical expert system is further developed for automatic ventilation therapy based on the well-known ARDSNet protocol by imposing additional dynamical constraints. This protocol-driven approach strengthens the overall treatment of patients with acute lung injury in terms of improving oxygenation dynamics. The proposed dynamics of quick action and long idleness are introduced on two independent ventilatory variables, namely fraction of inspiratory oxygen (FiO2) and positive end-expiratory pressure (PEEP). The therapeutic algorithm is realizable forming additional rules for automatic control of artificial ventilation for the treatment of acute respiratory distress syndrome (ARDS). Furthermore, the proposed algorithm is applicable in real clinical practice. A validation test was performed on a 52-kg induced-ARDS pig with outstanding results to meet all ventilation goals.
CRIS-Team Scopus Importer:2022-11-17

Automatisierte PEEP-Titration und Beatmung - Pickerodt, P. A.; Ruli, M.; Boemke, W.; Francis, Roland C. E. (Journal für Anasthesie und Intensivbehandlung, 2018)
CRIS-Team Scopus Importer:2022-11-17

Carbonic anhydrase is not a relevant nitrite reductase or nitrous anhydrase in the lung - Pickerodt, Philipp A.; Kronfeldt, Sebastian; Russ, Martin; Gonzalez-Lopez, Adrian; Lother, Philipp; Steiner, Elvira; Vorbrodt, Katja; Busch, Thilo; Boemke, Willehad; Francis, Roland C. E.; Swenson, Erik R. (The Journal of Physiology, 2019)
Key points: Carbonic anhydrase (CA) inhibitors such as acetazolamide inhibit hypoxic pulmonary vasoconstriction (HPV) in humans and other mammals, but the mechanism of this action remains unknown. It has been postulated that carbonic anhydrase may act as a nitrous anhydrase in vivo to generate nitric oxide (NO) from nitrite and that this formation is increased in the presence of acetazolamide. Acetazolamide reduces HPV in pigs without evidence of any NO generation, whereas nebulized sodium nitrite reduces HPV by NO formation; however; combined infusion of acetazolamide with sodium nitrite inhalation did not further increase exhaled NO concentration over inhaled nitrite alone in pigs exposed to alveolar hypoxia. We conclude that acetazolamide does not function as either a nitrous anhydrase or a nitrite reductase in the lungs of pigs, and probably other mammals, to explain its vasodilating actions in the pulmonary or systemic circulations. Abstract: The carbonic anhydrase (CA) inhibitors acetazolamide and its structurally similar analogue methazolamide prevent or reduce hypoxic pulmonary vasoconstriction (HPV) in dogs and humans in vivo, by a mechanism unrelated to CA inhibition. In rodent blood and isolated blood vessels, it has been reported that inhibition of CA leads to increased generation of nitric oxide (NO) from nitrite and vascular relaxation in vitro. We tested the physiological relevance of augmented NO generation by CA from nitrite with acetazolamide in anaesthetized pigs during alveolar hypoxia in vivo. We found that acetazolamide prevents HPV in anaesthetized pigs, as in other mammalian species. A single nebulization of sodium nitrite reduces HPV, but this action wanes in the succeeding 3 h of hypoxia as nitrite is metabolized and excreted. Pulmonary artery pressure reduction and NO formation as measured by exhaled gas concentration from inhaled sodium nitrite were not increased by acetazolamide during alveolar hypoxia. Thus, our data argue against a physiological role of carbonic anhydrase as a nitrous anhydrase or nitrite reductase as a mechanism for its inhibition of HPV in the lung and blood in vivo.
CRIS-Team Scopus Importer:2022-11-17
Keywords: acetazolamide; carbonic anhydrase; hypoxia; hypoxic pulmonary vasoconstriction; nitrite; pig

Closed-loop mechanical ventilation for lung injury: a novel physiological-feedback mode following the principles of the open lung concept - Schwaiberger, David; Pickerodt, Philipp A.; Pomprapa, Anake; Tjarks, Onno; Kork, Felix; Boemke, Willehad; Francis, Roland C. E.; Leonhardt, Steffen; Lachmann, Burkhard (Journal of Clinical Monitoring and Computing, 2018)
Adherence to low tidal volume (VT) ventilation and selected positive end-expiratory pressures are low during mechanical ventilation for treatment of the acute respiratory distress syndrome. Using a pig model of severe lung injury, we tested the feasibility and physiological responses to a novel fully closed-loop mechanical ventilation algorithm based on the “open lung” concept. Lung injury was induced by surfactant washout in pigs (n = 8). Animals were ventilated following the principles of the “open lung approach” (OLA) using a fully closed-loop physiological feedback algorithm for mechanical ventilation. Standard gas exchange, respiratory- and hemodynamic parameters were measured. Electrical impedance tomography was used to quantify regional ventilation distribution during mechanical ventilation. Automatized mechanical ventilation provided strict adherence to low VT-ventilation for 6 h in severely lung injured pigs. Using the “open lung” approach, tidal volume delivery required low lung distending pressures, increased recruitment and ventilation of dorsal lung regions and improved arterial blood oxygenation. Physiological feedback closed-loop mechanical ventilation according to the principles of the open lung concept is feasible and provides low tidal volume ventilation without human intervention. Of importance, the “open lung approach”-ventilation improved gas exchange and reduced lung driving pressures by opening atelectasis and shifting of ventilation to dorsal lung regions.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Acute respiratory distress syndrome; Closed-loop mechanical ventilation; Electrical impedance tomography; Lung protective ventilation; Open lung approach

Der Wissenschaftliche Arbeitskreis „Wissenschaftlicher Nachwuchs“ der Deutschen Gesellschaft für Anästhesiologie und Intensivmedizin - Bitzinger, Diane; Drexler, Berthold; Francis, Roland C. E.; Hubrath, Margarete; Larmann, Jan; Nau, Carla; Redel, Andreas; Roewer, Norbert; Stehr, Sebastian; Thal, Serge; Theilmeier, Gregor; Urban, Bernd (AINS - Anästhesiologie. Intensivmedizin. Notfallmedizin. Schmerztherapie., 2011)
CRIS-Team Scopus Importer:2022-11-17

Detection of catecholamines and metanephrines by radio-immunoassay in canine plasma - Francis, Roland C. E.; Pickerodt, Philipp A.; Salewski, Lothar; Boemke, Willehad; Hoehne, Claudia (Veterinary Journal, 2010)
This study investigated the applicability of two human radio-immunoassays (RIA) to detect epinephrine (EPI), norepinephrine (NE), and their O-methylated metabolites metanephrine (MN) and normetanephrine (NMN) in canine plasma. The analysis yielded a positive correlation between metabolites and their respective parent compounds: EPI and MN (r = 0.63), NE and NMN (r = 0.47), as well as between parent compounds, EPI and NE (r = 0.48), and between metabolites MN and NMN (r = 0.71). Moreover, EPI (r = 0.99) and NE (r = 0.77) concentrations determined by RIA did correlate positively with high pressure liquid chromatography (HPLC). However, there was limited agreement between both methods. It was concluded that complete validation tests for accuracy, precision and agreement are needed before this RIA can be applied to quantify catecholamines, metanephrine, and normetanephrine in canine plasma. The assay may prove to be a potential alternative to HPLC or tandem mass spectrometry in the work-up of pheochromocytoma and the detection of overall sympathetic activity in dogs. © 2008 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Catecholamine; Dog; Metanephrine; Normetanephrine; Radio immunoassay

Effects of a standard operating procedure on prehospital emergency care of patients presenting with symptoms of the acute coronary syndrome - Francis, Roland C. E.; Bubser, Florian; Schmidbauer, Willi; Spies, Claudia D.; Soerensen, Marc; Bosse, Goetz; Kerner, Thoralf (European Journal of Emergency Medicine, 2014)
To determine whether a standard operating procedure (SOP) for prehospital management of patients with the acute coronary syndrome (ACS) improves the quality of patient care in terms of adherence to treatment guidelines of the European Society of Cardiology. Among a total of 1025 patient medical records collected from a period before and after the introduction of the SOP, 269 records included the working diagnosis of ACS and were then reviewed for guideline adherence. Most aspects of patient evaluation, monitoring, treatment, and hospital allocation were fairly guideline adherent (>70%) before the SOP was introduced and were not affected by the SOP. The percentage of cases in whom sublingual nitrate (55.2 vs. 66.7%) or intravenous morphine (26.9 vs. 43.0%) was administered without contraindications was higher after the SOP had been introduced. Therefore, the use of an SOP in prehospital emergency medicine can partly improve the adherence to guideline recommendations for the treatment of patients with ACS. © 2014 Wolters Kluwer Health | Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2022-11-17
Keywords: acute coronary syndrome; emergency medicine; guideline adherence; standard

End-of-life decision-making in intensive care ten years after a law on advance directives in Germany - Graw, Jan A.; Marsch, Fanny; Spies, Claudia D.; Francis, Roland C. E. (Medicina, 2021)
Background and Objectives: Mortality on Intensive Care Units (ICUs) is high and death frequently occurs after decisions to limit life-sustaining therapies. An advance directive is a tool meant to preserve patient autonomy by guiding anticipated future treatment decisions once decision-making capacity is lost. Since September 2009, advance directives are legally binding for the caregiver team and the patients’ surrogate decision-maker in Germany. The change in frequencies of end-of-life decisions (EOLDs) and completed advance directives among deceased ICU patients ten years after the enactment of a law on advance directives in Germany is unknown. Materials and Methods: Retrospective analysis on all deceased patients of surgical ICUs of a German university medical center from 08/2008 to 09/2009 and from 01/2019 to 09/2019. Frequency of EOLDs and advance directives and the process of EOLDs were compared between patients admitted before and after the change in legislation. (No. of ethical approval EA2/308/20) Results: Significantly more EOLDs occurred in the 2019 cohort compared to the 2009 cohort (85.8% vs. 70.7% of deceased patients, p = 0.006). The number of patients possessing an advance directive to express a living or therapeutic will was higher in the 2019 cohort compared to the 2009 cohort (26.4% vs. 8.9%; difference: 17.5%, p < 0.001). Participation of the patients’ family in the EOLD process (74.7% vs. 60.9%; difference: 13.8%, p = 0.048) and the frequency of documentation of EOLD-relevant information (50.0% vs. 18.7%; difference: 31.3%, p < 0.001) increased from 2009 to 2019. Discussion: During a ten-year period from 2009 to 2019, the frequency of EOLDs and the completion rate of advance directives have increased considerably. In addition, EOLD-associated communication and documentation have further improved.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Advance directive; End-of-life decision; Intensive care unit; Shared decision-making

Endothelin receptor subtype A blockade does not affect the haemodynamic recovery from haemorrhage during xenon/remifentanil or isoflurane/remifentanil anaesthesia in dogs - Francis, Roland C. E.; Hoehne, Claudia; Klein, Adrian; Kaisers, Udo X.; Pickerodt, Philipp A.; Boemke, Willehad (Veterinary Anaesthesia and Analgesia, 2010)
Objective: To test the compensatory role of endothelin-1 when acute blood loss is superimposed on anaesthesia, by characterizing the effect of systemic endothelin receptor subtype A (ETA) blockade on the haemodynamic and hormonal responses to haemorrhage in dogs anaesthetized with xenon/remifentanil (X/R) or isoflurane/remifentanil (I/R). Study design: Prospective experimental randomized controlled study. Animals: Six female Beagle dogs, 13.4 ± 1.3 kg. Methods: Animals were anaesthetized with remifentanil 0.5 μg kg-1 minute-1 plus either 0.8% isoflurane (I/R) or 63% xenon (X/R), with and without (Control) the systemic intravenous endothelin receptor subtype A antagonist atrasentan (four groups, n = 6 each). After 60 minutes of baseline anaesthesia, the dogs were bled (20 mL kg-1) over 5 minutes and hypovolemia was maintained for 1 hour. Continuous haemodynamic monitoring was performed via femoral and pulmonary artery catheters; vasoactive hormones were measured before and after haemorrhage. Results: In Controls, systemic vascular resistance (SVR), vasopressin and catecholamine plasma concentrations were higher with X/R than with I/R anaesthesia at pre-haemorrhage baseline. The peak increase after haemorrhage was higher during X/R than during I/R anaesthesia (SVR 7420 ± 867 versus 5423 ± 547 dyne seconds cm-5; vasopressin 104 ± 23 versus 44 ± 6 pg mL-1; epinephrine 2956 ± 310 versus 177 ± 99 pg mL-1; norepinephrine 862 ± 117 versus 195 ± 33 pg mL-1, p < 0.05). Haemorrhage reduced central venous pressure from 3 ± 1 to 1 ± 1 cmH2O (I/R, ns) and from 8 ± 1 to 5 ± 1 cmH2O (X/R, p < 0.05), but did not reduce mean arterial pressure, nor cardiac output. Atrasentan did not alter the haemodynamic and hormonal response to haemorrhage during either anaesthetic protocol. Conclusions and clinical relevance: Selective ETA receptor blockade with atrasentan did not impair the haemodynamic and hormonal compensation of acute haemorrhage during X/R or I/R anaesthesia in dogs. © 2010 The Authors. Journal compilation © 2010 Association of Veterinary Anaesthetists.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Anaesthesia; Atrasentan; Catecholamines; Dog; Haemorrhage; Xenon

Erratum to: Intraoperative transösophageale Echokardiographie in der Herzchirurgie mit Fokus auf die Mitralklappenrekonstruktion (Zeitschrift für Herz-,Thorax- und Gefäßchirurgie, (2024), 38, 1, (37-51), 10.1007/s00398-023-00631-0) - Krajinovic, Ljubica; Fechner, Jörg; Einhaus, Friedrich; Francis, Roland; Nooh, Ehab; Czesla, M.; Dewald, Oliver; Heim, Christian (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2024)
CRIS-Team Scopus Importer:2024-03-29

Extracorporeal Membrane Oxygenation Blood Flow and Blood Recirculation Compromise Thermodilution-Based Measurements of Cardiac Output - Russ, Martin; Steiner, Elvira; Boemke, Willehad; Busch, Thilo; Melzer-Gartzke, Christoph; Taher, Mahdi; Badulak, Jenelle; Weber-Carstens, Steffen; Swenson, Erik R.; Francis, Roland C. E.; Pickerodt, Philipp A. (Asaio Journal, 2022)
The contribution of veno-venous (VV) extracorporeal membrane oxygenation (ECMO) to systemic oxygen delivery is determined by the ratio of total extracorporeal blood flow (Q˙EC) to cardiac output (Q˙). Thermodilution-based measurements of Q˙ may be compromised by blood recirculating through the ECMO (recirculation fraction; Rf). We measured the effects of Q˙EC and Rf on classic thermodilution-based measurements of Q˙ in six anesthetized pigs. An ultrasound flow probe measured total aortic blood flow (Q˙A0) at the aortic root. Rf was quantified with the ultrasound dilution technique. Q˙EC was set to 0-125% of Q˙A0 and Q˙ was measured using a pulmonary artery catheter (PAC) in healthy and lung injured animals. PAC overestimated Q˙ (Q˙Pa) at all Q˙EC settings compared to Q˙A0. The mean bias between both methods was 2.1 L/min in healthy animals and 2.7 L/min after lung injury. The difference between Q˙Pa and Q˙A0 increased with an Q˙EC of 75-125%/Q˙A0 compared to QEC<50%/Q˙A0. Overestimation of Q˙Pa was highest when Q˙EC resulted in a high Rf. Thus, thermodilution-based measurements can overestimate cardiac output during VV ECMO. The degree of overestimation of Q˙Pa depends on the Q˙EC/Q˙A0 ratio and the recirculation fraction.
CRIS-Team Scopus Importer:2022-11-17
Keywords: acute lung injury; cardiac output measurements; extracorporeal membrane oxygenation; recirculation fraction; thermodilution; veno-venous

Increased intracranial pressure: An interdisciplinary challenge in the operating room and intensive care unit Der erhhöte intrakranielle Druck Eine interdisziplinäre Herausforderung im OP und auf der Intensivstation - Weber-Carstens, Steffen; Francis, Roland C. E.; Spies, Claudia D. (AINS - Anästhesiologie. Intensivmedizin. Notfallmedizin. Schmerztherapie., 2012)
CRIS-Team Scopus Importer:2022-11-17

Induction of severe hypoxemia and low lung recruitability for the evaluation of therapeutic ventilation strategies: a translational model of combined surfactant-depletion and ventilator-induced lung injury - Boerger, Emilia; Russ, Martin; Von Platen, Philip; Taher, Mahdi; Hinken, Lea; Pomprapa, Anake; Koebrich, Rainer; Konietschke, Frank; Graw, Jan Adriaan; Lachmann, Burkhard; Braun, Wolfgang; Leonhardt, Steffen; et al. (Intensive Care Medicine Experimental, 2022)
Background: Models of hypoxemic lung injury caused by lavage-induced pulmonary surfactant depletion are prone to prompt recovery of blood oxygenation following recruitment maneuvers and have limited translational validity. We hypothesized that addition of injurious ventilation following surfactant-depletion creates a model of the acute respiratory distress syndrome (ARDS) with persistently low recruitability and higher levels of titrated “best” positive end-expiratory pressure (PEEP) during protective ventilation. Methods: Two types of porcine lung injury were induced by lung lavage and 3 h of either protective or injurious ventilation, followed by 3 h of protective ventilation (N = 6 per group). Recruitment maneuvers (RM) and decremental PEEP trials comparing oxygenation versus dynamic compliance were performed after lavage and at 3 h intervals of ventilation. Pulmonary gas exchange function, respiratory mechanics, and ventilator-derived parameters were assessed after each RM to map the course of injury severity and recruitability. Results: Lung lavage impaired respiratory system compliance (Crs) and produced arterial oxygen tensions (PaO2) of 84±13 and 80±15 (FIO2 = 1.0) with prompt increase after RM to 270–395 mmHg in both groups. After subsequent 3 h of either protective or injurious ventilation, PaO2/FIO2 was 104±26 vs. 154±123 and increased to 369±132 vs. 167±87 mmHg in response to RM, respectively. After additional 3 h of protective ventilation, PaO2/FIO2 was 120±15 vs. 128±37 and increased to 470±68 vs. 185±129 mmHg in response to RM, respectively. Subsequently, decremental PEEP titration revealed that Crs peaked at 36 ± 10 vs. 25 ± 5 ml/cm H2O with PEEP of 12 vs. 16 cmH2O, and PaO2/FIO2 peaked at 563 ± 83 vs. 334 ± 148 mm Hg with PEEP of 16 vs. 22 cmH2O in the protective vs. injurious ventilation groups, respectively. The large disparity of recruitability between groups was not reflected in the Crs nor the magnitude of mechanical power present after injurious ventilation, once protective ventilation was resumed. Conclusion: Addition of transitory injurious ventilation after lung lavage causes prolonged acute lung injury with diffuse alveolar damage and low recruitability yielding high titrated PEEP levels. Mimicking lung mechanical and functional characteristics of ARDS, this porcine model rectifies the constraints of single-hit lavage models and may enhance the translation of experimental research on mechanical ventilation strategies.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Acute lung injury; Acute respiratory distress syndrome; Closed-loop ventilation; Mechanical power; Recruitment maneuver; Surfactant depletion; Ventilator-induced lung injury

Inhaled nitric oxide reduces endothelial activation and parasite accumulation in the brain, and enhances survival in experimental cerebral malaria - Serghides, Lena; Kim, Hani; Lu, Ziyue; Kain, Dylan C.; Miller, Chris; Francis, Roland C.; Liles, W. Conrad; Zapol, Warren M.; Kain, Kevin C. (PLoS ONE, 2011)
The host immune response contributes to the onset and progression of severe malaria syndromes, such as cerebral malaria. Adjunctive immunomodulatory strategies for severe malaria may improve clinical outcome beyond that achievable with artemisinin-based therapy alone. Here, we report that prophylaxis with inhaled nitric oxide significantly reduced systemic inflammation (lower TNF, IFNγ and MCP-1 in peripheral blood) and endothelial activation (decreased sICAM-1 and vWF, and increased angiopoeitin-1 levels in peripheral blood) in an experimental cerebral malaria model. Mice that received inhaled nitric oxide starting prior to infection had reduced parasitized erythrocyte accumulation in the brain, decreased brain expression of ICAM-1, and preserved vascular integrity compared to control mice. Inhaled nitric oxide administered in combination with artesunate, starting as late as 5.5 days post-infection, improved survival over treatment with artesunate alone (70% survival in the artesunate only vs. 100% survival in the artesunate plus iNO group, p = 0.03). These data support the clinical investigation of inhaled nitric oxide as a novel adjunctive therapy in patients with severe malaria. © 2011 Serghides et al.
CRIS-Team Scopus Importer:2022-11-17

Intraoperative transösophageale Echokardiographie in der Herzchirurgie mit Fokus auf die Mitralklappenrekonstruktion - Krajinovic, Ljubica; Fechner, Jörg; Einhaus, Friedrich; Francis, Roland; Nooh, Ehab; Czesla, M.; Dewald, Oliver; Heim, Christian (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2024)
Transesophageal echocardiography (TEE) is important for rapid assessment of biventricular function, regional contractility disorders and the integrity of heart valve anatomy and function. Mitral valve regurgitation (MVR) is the second most common valvular heart disease in Europe after aortic valve stenosis. Qualified TEE is indispensable for the success of minimally invasive repair of severe MVR (MIR-MVR). For quantification of MVR the vena contracta area, effective regurgitant orifice area (EROA) determined using the proximal isovelocity surface area (PISA), regurgitant volume and left ventricular endsystolic diameter are utilized for quantification of MVR. Grading of the MVR, the final assessment of the operation results and echocardiographic guidance during critical surgical steps of MIR-MVR are essential. The MIR-MVR is complex and requires an optimal interdisciplinary cooperation.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Diagnostic imaging; Endoaortic occlusion; Heart-lung machine; Minimally invasive surgical procedures; Mitral valve regurgitation

In vitro validation and characterization of pulsed inhaled nitric oxide administration during early inspiration - Pickerodt, Philipp A.; Hofferberth, Moritz B. T.; Busch, Thilo; Russ, Martin; Taher, Mahdi; Boemke, Willehad; Weber-Carstens, Steffen; Koebrich, Rainer; Swenson, Erik; Deja, Maria; Francis, Roland C. E. (Journal of Clinical Monitoring and Computing, 2022)
Purpose: Admixture of nitric oxide (NO) to the gas inspired with mechanical ventilation can be achieved through continuous, timed, or pulsed injection of NO into the inspiratory limb. The dose and timing of NO injection govern the inspired and intrapulmonary effect site concentrations achieved with different administration modes. Here we test the effectiveness and target reliability of a new mode injecting pulsed NO boluses exclusively during early inspiration. Methods: An in vitro lung model was operated under various ventilator settings. Admixture of NO through injection into the inspiratory limb was timed either (i) selectively during early inspiration (“pulsed delivery”), or as customary, (ii) during inspiratory time or (iii) the entire respiratory cycle. Set NO target concentrations of 5–40 parts per million (ppm) were tested for agreement with the yield NO concentrations measured at various sites in the inspiratory limb, to assess the effectiveness of these NO administration modes. Results: Pulsed delivery produced inspiratory NO concentrations comparable with those of customary modes of NO administration. At low (450 ml) and ultra-low (230 ml) tidal volumes, pulsed delivery yielded better agreement of the set target (up to 40 ppm) and inspiratory NO concentrations as compared to customary modes. Pulsed delivery with NO injection close to the artificial lung yielded higher intrapulmonary NO concentrations than with NO injection close to the ventilator. The maximum inspiratory NO concentration observed in the trachea (68 ± 30 ppm) occurred with pulsed delivery at a set target of 40 ppm. Conclusion: Pulsed early inspiratory phase NO injection is as effective as continuous or non-selective admixture of NO to inspired gas and may confer improved target reliability, especially at low, lung protective tidal volumes.
CRIS-Team Scopus Importer:2022-11-17
Keywords: ARDS; Artificial lung; Inhalation; Mechanical ventilation; Nitric oxide; PiNO

Lavage-induced surfactant depletion in pigs as a model of the acute respiratory distress syndrome (ARDS) - Russ, Martin; Kronfeldt, Sebastian; Boemke, Willehad; Busch, Thilo; Francis, Roland C. E.; Pickerodt, Philipp A. (Journal of Visualized Experiments, 2016)
Various animal models of lung injury exist to study the complex pathomechanisms of human acute respiratory distress syndrome (ARDS) and evaluate future therapies. Severe lung injury with a reproducible deterioration of pulmonary gas exchange and hemodynamics can be induced in anesthetized pigs using repeated lung lavages with warmed 0.9% saline (50 ml/kg body weight). Including standard respiratory and hemodynamic monitoring with clinically applied devices in this model allows the evaluation of novel therapeutic strategies (drugs, modern ventilators, extracorporeal membrane oxygenators, ECMO), and bridges the gap between bench and bedside. Furthermore, induction of lung injury with lung lavages does not require the injection of pathogens/endotoxins that impact on measurements of pro- and anti-inflammatory cytokines. A disadvantage of the model is the high recruitability of atelectatic lung tissue. Standardization of the model helps to avoid pitfalls, to ensure comparability between experiments, and to reduce the number of animals needed.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Acute respiratory distress syndrome; Animal model; ARDS; Issue 115; Lung injury; Lung lavage; Medicine; Pig; Surfactant washout

Liberal transfusion strategy to prevent mortality and anaemia-associated, ischaemic events in elderly non-cardiac surgical patients - The study design of the LIBERAL-Trial - Meybohm, Patrick; Lindau, Simone; Treskatsch, Sascha; Francis, Roland C. E.; Spies, Claudia; Velten, Markus; Wittmann, Maria; Gueresir, Erdem; Stoppe, Christian; Kowark, Ana; Coburn, Mark; Selleng, Sixten; et al. (Trials, 2019)
Background: Perioperative anaemia leads to impaired oxygen supply with a risk of vital organ ischaemia. In healthy and fit individuals, anaemia can be compensated by several mechanisms. Elderly patients, however, have less compensatory mechanisms because of multiple co-morbidities and age-related decline of functional reserves. The purpose of the study is to evaluate whether elderly surgical patients may benefit from a liberal red blood cell (RBC) transfusion strategy compared to a restrictive transfusion strategy. Methods: The LIBERAL Trial is a prospective, randomized, multicentre, controlled clinical phase IV trial randomising 2470 elderly (≥ 70 years) patients undergoing intermediate- or high-risk non-cardiac surgery. Registered patients will be randomised only if Haemoglobin (Hb) reaches ≤9 g/dl during surgery or within 3 days after surgery either to the LIBERAL group (transfusion of a single RBC unit when Hb ≤ 9 g/dl with a target range for the post-transfusion Hb level of 9-10.5 g/dl) or the RESTRICTIVE group (transfusion of a single RBC unit when Hb ≤ 7.5 g/dl with a target range for the post-transfusion Hb level of 7.5-9 g/dl). The intervention per patient will be followed until hospital discharge or up to 30 days after surgery, whichever occurs first. The primary efficacy outcome is defined as a composite of all-cause mortality, acute myocardial infarction, acute ischaemic stroke, acute kidney injury (stage III), acute mesenteric ischaemia and acute peripheral vascular ischaemia within 90 days after surgery. Infections requiring iv antibiotics with re-hospitalisation are assessed as important secondary endpoint. The primary endpoint will be analysed by logistic regression adjusting for age, cancer surgery (y/n), type of surgery (intermediate- or high-risk), and incorporating centres as random effect. Discussion: The LIBERAL-Trial will evaluate whether a liberal transfusion strategy reduces the occurrence of major adverse events after non-cardiac surgery in the geriatric population compared to a restrictive strategy within 90 days after surgery. Trial registration: ClinicalTrials.gov (identifier: NCT03369210).
CRIS-Team Scopus Importer:2022-11-17
Keywords: anaemia; elderly patients; Red blood cell transfusion; surgery

Long-term survival after extracorporeal membrane oxygenation therapy: The attention it deserves! - Pickerodt, Philipp A.; Francis, Roland C. E.; Weber-Carstens, Steffen (Critical Care Medicine, 2017)
CRIS-Team Scopus Importer:2022-11-17
Keywords: acute respiratory distress syndrome; extracorporeal membrane oxygenation; long-term survival; outcome

Lower versus higher hemoglobin threshold for transfusion in ARDS patients with and without ECMO - Hunsicker, Oliver; Materne, Lorenz; Buenger; Krannich, Alexander; Balzer, Felix; Spies, Claudia; Francis, Roland C. E.; Weber-Carstens, Steffen; Menk, Mario; Graw, J. A. (Critical Care, 2020)
Background: Efficacy and safety of different hemoglobin thresholds for transfusion of red blood cells (RBCs) in adults with an acute respiratory distress syndrome (ARDS) are unknown. We therefore assessed the effect of two transfusion thresholds on short-term outcome in patients with ARDS. Methods: Patients who received transfusions of RBCs were identified from a cohort of 1044 ARDS patients. After propensity score matching, patients transfused at a hemoglobin concentration of 8 g/dl or less (lower-threshold) were compared to patients transfused at a hemoglobin concentration of 10 g/dl or less (higher-threshold). The primary endpoint was 28-day mortality. Secondary endpoints included ECMO-free, ventilator-free, sedation-free, and organ dysfunction-free composites. Measurements and main results: One hundred ninety-two patients were eligible for analysis of the matched cohort. Patients in the lower-threshold group had similar baseline characteristics and hemoglobin levels at ARDS onset but received fewer RBC units and had lower hemoglobin levels compared with the higher-threshold group during the course on the ICU (9.1 [IQR, 8.7–9.7] vs. 10.4 [10–11] g/dl, P < 0.001). There was no difference in 28-day mortality between the lower-threshold group compared with the higher-threshold group (hazard ratio, 0.94 [95%-CI, 0.59–1.48], P = 0.78). Within 28 days, 36.5% (95%-CI, 27.0–46.9) of the patients in the lower-threshold group compared with 39.5% (29.9–50.1) of the patients in the higher-threshold group had died. While there were no differences in ECMO-free, sedation-free, and organ dysfunction-free composites, the chance for successful weaning from mechanical ventilation within 28 days after ARDS onset was lower in the lower-threshold group (subdistribution hazard ratio, 0.36 [95%-CI, 0.15–0.86], P = 0.02). Conclusions: Transfusion at a hemoglobin concentration of 8 g/dl, as compared with a hemoglobin concentration of 10 g/dl, was not associated with an increase in 28-day mortality in adults with ARDS. However, a transfusion at a hemoglobin concentration of 8 g/dl was associated with a lower chance for successful weaning from the ventilator during the first 28 days after ARDS onset. Trial Registration: ClinicalTrials.gov NCT03871166.
CRIS-Team Scopus Importer:2022-11-17
Keywords: ARDS; Red blood cells; Transfusion

Lung Purinoceptor Activation Triggers Ventilator-Induced Brain Injury - Gonzalez-Lopez, Adrian; Lopez-Alonso, Ines; Pickerodt, Philipp A.; Von Haefen, Clarissa; Amado-Rodriguez, Laura; Reimann, Henning; Niendorf, Thoralf; Kuebler, Wolfgang; Albaiceta, Guillermo M.; Francis, Roland C. E.; Spies, Claudia D. (Critical Care Medicine, 2019)
OBJECTIVES: Mechanical ventilation can cause ventilator-induced brain injury via afferent vagal signaling and hippocampal neurotransmitter imbalances. The triggering mechanisms for vagal signaling during mechanical ventilation are unknown. The objective of this study was to assess whether pulmonary transient receptor potential vanilloid type-4 (TRPV4) mechanoreceptors and vagal afferent purinergic receptors (P2X) act as triggers of ventilator-induced brain injury. DESIGN: Controlled, human in vitro and ex vivo studies, as well as murine in vivo laboratory studies. SETTING: Research laboratory. SUBJECTS: Wild-type, TRPV4-deficient C57BL/6J mice, 8-10 weeks old. Human postmortem lung tissue and human lung epithelial cell line BEAS-2B. INTERVENTION: Mice subjected to mechanical ventilation were studied using functional MRI to assess hippocampal activity. The effects of lidocaine (a nonselective ion-channel inhibitor), P2X-purinoceptor antagonist (iso-PPADS), or genetic TRPV4 deficiency on hippocampal dopamine-dependent pro-apoptotic signaling were studied in mechanically ventilated mice. Human lung epithelial cells (BEAS-2B) were used to study the effects of mechanical stretch on TRPV4 and P2X expression and activation. TRPV4 levels were measured in postmortem lung tissue from ventilated and nonventilated patients. MEASUREMENTS AND MAIN RESULTS: Hippocampus functional MRI analysis revealed considerable changes in response to the increase in tidal volume during mechanical ventilation. Intratracheal lidocaine, iso-PPADS, and TRPV4 genetic deficiency protected mice against ventilationinduced hippocampal pro-apoptotic signaling. Mechanical stretch in both, BEAS-2B cells and ventilated wild-type mice, resulted in TRPV4 activation and reduced Trpv4 and P2x expression. Intratracheal replenishment of adenosine triphosphate in Trpv4 mice abrogated the protective effect of TRPV4 deficiency. Autopsy lung tissue from ventilated patients showed decreased lung TRPV4 levels compared with nonventilated CONCLUSIONS:: TRPV4 mechanosensors and purinergic receptors are involved in the mechanisms of ventilator-induced brain injury. Inhibition of this neural signaling, either using nonspecific or specific inhibitors targeting the TRPV4/adenosine triphosphate/P2X signaling axis, may represent a novel strategy to prevent or treat ventilator-induced brain injury.
CRIS-Team Scopus Importer:2022-11-17

Monitoring of the respiratory muscle function during weaning from mechanical ventilation Respiratorentwöhnung - Die Atemmuskelpumpe - Bedeutung für die Respiratorentwöhnung - Pickerodt, Philipp A.; Francis, Roland C. E.; Weber-Carstens, Steff (AINS - Anästhesiologie. Intensivmedizin. Notfallmedizin. Schmerztherapie., 2013)
Early weaning and discontinuation of mechanical ventilation can help prevent respiratory muscle dysfunction in critically ill patients. Prolonged mechanical ventilation and failure to use adequate strategies to discontinue mechanical ventilation can even enhance and perpetuate respiratory muscle dysfunction. On the other hand, premature attempts to extubate may result in re-intubation due to respiratory failure and are associated with poor outcomes and high mortality rates of up to 30-50%. Therefore, accurate monitoring of the respiratory muscle function is a valuable tool for the clinician at the bedside to assess to optimal weaning strategy and, ideally, would predict either weaning failure or success. In this review, we briefly summarize the available techniques, measurements and equipment required for the monitoring of respiratory muscle function in the intensive care unit.
CRIS-Team Scopus Importer:2022-11-17
Keywords: discontinuation of mechanical ventilation; monitoring of respiratory muscle function; rapid shallow breathing index; weaning

Nitric oxide synthase 3 contributes to ventilator-induced lung injury - Vaporidi, Katerina; Francis, Roland C. E.; Bloch, Kenneth D.; Zapol, Warren M. (American Journal of Physiology-Lung Cellular and Molecular Physiology, 2010)
Nitric oxide synthase (NOS) depletion or inhibition reduces ventilator-induced lung injury (VILI), but the responsible mechanisms remain incompletely defined. The aim of this study was to elucidate the role of endothelial NOS, NOS3, in the pathogenesis of VILI in an in vivo mouse model. Wild-type and NOS3-deficient mice were ventilated with high-tidal volume (HVT; 40 ml/kg) for 4 h, with and without adding NO to the inhaled gas. Additional wild-type mice were pretreated with tetrahydrobiopterin and ascorbic acid, agents that can prevent NOS-generated superoxide production. Arterial blood gas tensions, histology, and lung mechanics were evaluated after 4 h of HVT ventilation. The concentration of protein, IgM, cytokines, malondialdehyde, and 8-isoprostane were measured in bronchoalveolar lavage fluid (BALF). Myeloperoxidase activity, total and oxidized glutathione levels, and NOS-derived superoxide production were measured in lung tissue homogenates. HVT ventilation induced VILI in wild-type mice, as reflected by decreased lung compliance, increased concentrations of protein and cytokines in BALF, and oxidative stress. All indices of VILI were ameliorated in NOS3-deficient mice. Augmenting pulmonary NO levels by breathing NO during mechanical ventilation did not increase lung injury in NOS3-deficient mice. HVT ventilation increased NOS-inhibitable superoxide production in lung extracts from wild-type mice but not in those from NOS3-deficient mice. Administration of tetrahydrobiopterin and ascorbic acid ameliorated VILI in wild-type mice. Our results indicate that NOS3 contributes to ventilator-induced lung injury via increased production of superoxide. Copyright © 2010 the American Physiological Society.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Inflammation; Pulmonary edema; Superoxide

Perioperative myocardial ischemia—a disparity between diagnoses and treatment options? Perioperative Myokardischämien – ein Missverhältnis zwischen Diagnosen und Therapiemöglichkeiten? - Francis, Roland C. E.; Tafelski, Sascha; Moeckel, Martin (Anaesthesist, 2019)
CRIS-Team Scopus Importer:2022-11-17

Pharmacokinetics of Oral and Intravenous Oseltamivir Treatment of Severe Influenza B Virus Infection Requiring Organ Replacement Therapy - Karsch, Katharina; Chen, Xi; Miera, Oliver; Peters, Bjoern; Obermeier, Patrick; Francis, Roland C. E.; Amann, Valerie; Duwe, Susanne; Fraaij, Pieter; Heider, Alla; De Zwart, Marcel; Berger, Felix; et al. (European Journal of Drug Metabolism and Pharmacokinetics, 2017)
Background and Objectives: Patients with severe influenza virus infection, multi-organ failure and organ replacement therapy may absorb and metabolize neuraminidase inhibitors differently. Systematic pharmacokinetic/pharmacodynamic clinical trials are currently lacking in this high-risk group. Inadequate dosing increases the risk of treatment failure and drug resistance, especially in severely ill patients with elevated virus loads. This study aims to explore the impact of organ replacement therapy on oseltamivir drug concentrations. Methods: Serial pharmacokinetic/pharmacodynamic measurements and Sieving coefficients were assessed in two patients with severe influenza B infection requiring organ replacement therapy. Results: Patient #1, a 9-year-old female with severe influenza B virus infection, biventricular assist device, and continuous veno-venous hemodiafiltration, received 75 mg oral oseltamivir twice-daily for 2 days, then intravenous oseltamivir with one-time renoprotective dosing (40 mg), followed by regular intravenous administration of 100 mg twice-daily. Plasma oseltamivir carboxylate concentrations were stable initially, but only regular administration of 100 mg resulted in virus load decline and clinical improvement. Patient #2, a 28-year-old female with influenza B virus infection requiring extracorporeal membrane oxygenation, received 75 mg oral oseltamivir twice-daily, resulting in erratic oseltamivir blood concentrations. In both patients, drug concentrations remained well within safety margins. Conclusions: In severe cases with multi-organ failure, administration of 100 mg intravenous oseltamivir twice-daily provided reliable drug concentrations, as opposed to renoprotective and oral dosing, thereby minimizing the risk of treatment failure and drug resistance. Evidence-based pediatric dosing recommendations and effective intravenous antiviral treatment modalities are needed for intensive care patients with life-threatening influenza disease.
CRIS-Team Scopus Importer:2022-11-17

Point-of-Care diagnostics of coagulation in the management of bleeding and transfusion in trauma patients - Francis, Roland C. E.; Theurl, Igor; Maegele, Marc; Graw, Jan A. (Current Opinion in Anaesthesiology, 2020)
PURPOSE OF REVIEW: Trauma-associated bleeding and coagulopathy require timely identification, prevention, and effective treatment. The present review summarizes the recent literature around point-of-care (POC) coagulation tests, their usefulness in the management of trauma-induced coagulopathy (TIC), their impact on trauma patient outcomes, and the requirement of quality assurance. RECENT FINDINGS: Best practice algorithms to manage TIC have been compiled in the 2019 European Guideline on the management of major bleeding and coagulopathy after trauma. Evidence supports the use of goal-directed approaches to manage TIC. POC coagulation tests can accelerate and tailor individualized therapies. Recent findings emphasize: the time sparing of POC tests in prehospital settings and the validity of POC measurements in extreme environments; the potential scalability of POC-guided TIC algorithms in burn injuries and the pediatric population; the need for careful considerations of strategies to monitor and reverse the effects of direct oral anticoagulants in major trauma. SUMMARY: In contrast to an abundance of reviews and practical approaches to POC coagulation management in trauma patients, there is a scarcity of research in the field and large-scale clinical trials are urgently needed. The paneuropean multicenter trial Implementing Treatment Algorithms for the Correction of Trauma Induced Coagulopathy (iTACTIC) will inform on the potential of viscoelastic tests to augment transfusion protocols for better patient outcomes.
CRIS-Team Scopus Importer:2022-11-17

Prolonged unconsciousness after applying caudal anaesthesia Prolongierte Bewusstlosigkeit nach Anlage einer Kaudalanästhesie - Schulte, E.; Koch, S.; Schröder, J. T.; Tietze, A.; Binscheck-Domass, T.; Kramer, S.; Rothe, K.; Francis, Roland C. E. (Anästhesiologie & Intensivmedizin, 2018)
The application of caudal anaesthesia to the child is a commonly performed and a low-risk procedure in postoperative pain therapy. In the presence of anatomical variants such as a deepending dural sac, a sacral meningocele or a sacral meningeal cyst, however, the intrathecal application of the local anaesthetic and thus high spinal anaesthesia may occur. A negative aspiration test does not protect against this complication. Sonographic evaluation of the local anatomy and puncture site with ultrasound-guided needle insertion may increase the safety and efficacy of caudal anaesthesia. However, the specificity of sonography to detect sacral anatomical variants is limited. Other causes of prolonged unconsciousness after caudal anesthesia, e.g. metabolic causes, intoxication with local anaesthetics or cerebral pathologies are discussed.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Caudal Anaesthesia; High Spinal Anaesthesia; Local Anaesthetic Intoxication; Meningeal Cysts; Tarlow's Cysts

Protective and detrimental effects of sodium sulfide and hydrogen sulfide in murine ventilator-induced lung injury - Francis, Roland C. E.; Vaporidi, Katerina; Bloch, Kenneth D.; Ichinose, Fumito; Zapol, Warren M. (Anesthesiology, 2011)
Background: The antiinflammatory effects of hydrogen sulfide (H 2S) and sodium sulfide (Na2S) treatment may prevent acute lung injury induced by high tidal volume (HVT) ventilation. However, lung protection may be limited by direct pulmonary toxicity associated with H 2S inhalation. Therefore, the authors tested whether the inhalation of H2S or intravascular Na2S treatment can protect against ventilator-induced lung injury in mice. Methods: Anesthetized mice continuously inhaled 0, 1, 5, or 60 ppm H2S or received a single bolus infusion of Na2S (0.55 mg/kg) or vehicle and were then subjected to HVT (40 ml/kg) ventilation lasting 4 h (n = 4-8 per group). RESULTS:: HVT ventilation increased the concentrations of protein and interleukin-6 in bronchoalveolar lavage fluid, contributing to reduced respiratory compliance and impaired arterial oxygenation, and caused death from lung injury and pulmonary edema. Inhalation of 1 or 5 ppm H2S during HVT ventilation did not alter lung injury, but inhalation of 60 ppm H2S accelerated the development of ventilator-induced lung injury and enhanced the pulmonary expression of the chemoattractant CXCL-2 and the leukocyte adhesion molecules CD11b and L-selectin. In contrast, pretreatment with Na2S attenuated the expression of CXCL-2 and CD11b during HVT ventilation and reduced pulmonary edema. Moreover, Na2S enhanced the pulmonary expression of Nrf2-dependent antioxidant genes (NQO1, GPX2, and GST-A4) and prevented oxidative stress-induced depletion of glutathione in lung tissue. Conclusions: The data suggest that systemic intravascular treatment with Na2S represents a novel therapeutic strategy to prevent both ventilator-induced lung injury and pulmonary glutathione depletion by activating Nrf2-dependent antioxidant gene transcription. © 2011 the American Society of Anesthesiologists, Inc. Lippincott Williams & Wilkins. Anesthesiology.
CRIS-Team Scopus Importer:2022-11-17

Pulmonary vasodilation by acetazolamide during hypoxia: Impact of methyl-group substitutions and administration route in conscious, spontaneously breathing dogs - Pickerodt, Philipp A.; Francis, Roland C. E.; Hoehne, Claudia; Neubert, Friederike; Telalbasic, Stella; Boemke, Willehad; Swenson, Erik R. (Journal of Applied Physiology, 2014)
Acetazolamide (ACZ) prevents hypoxic pulmonary vasoconstriction (HPV) in isolated lungs, animals, and humans, but not by carbonic anhydrase (CA) inhibition. We studied administration routes in, and certain structural aspects of, ACZ critical to HPV inhibition. Analogs of ACZ during acute hypoxia were tested in unanesthetized dogs. Dogs breathed normoxic gas for 1 h (inspired O2 fraction = 0.21), followed by 10% O2 for 2 h (hypoxia) in these protocols: 1) controls; 2) ACZ intravenously (2 mg·kg-1·h -1); 3) ACZ orally (5 mg/kg, 12 and 1 h before the experiment); 4) inhaled ACZ (750 mg); 5) methazolamide (MTZ) intravenously (3 mg·kg -1·h-1); and 6) N-methyl-Acetazolamide (NMA) intravenously (10 mg·kg-1·h-1). In controls, mean pulmonary arterial pressure (MPAP) increased 7 mmHg, and pulmonary vascular resistance (PVR) 224 dyn·s·cm-5 with hypoxia (P < 0.05). With intravenous and inhaled ACZ, MPAP and PVR did not change during hypoxia. With oral ACZ, HPV was only slightly suppressed; MPAP increased 5 mmHg and PVR by 178 dyn·s·cm-5 during hypoxia. With MTZ and NMA, the MPAP rise (4 ± 2 mmHg) was reduced, and PVR did not increase during hypoxia compared with normoxia (MTZ intravenous: 81 ± 77 and 68 ± 82 dyn·s·cm-5 with NMA intravenous). Inhaled ACZ prevents HPV, but not without causing systemic CA inhibition. NMA, a compound lacking CA inhibiting effects by methylation at the sulfonamide moiety, and MTZ, a CA-inhibiting analog methylated at the thiadiazole ring, are only slightly less effective than ACZ in reducing HPV. Copyright © 2014 the American Physiological Society.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Acetazolamide; Hypoxic pulmonary vasoconstriction; N-methyl-Acet-Azolamide; Pulmonary arterial pressure; Pulmonary vascular resistance

Revisiting the impact of red cell storage duration on adverse outcomes after transfusion - Graw, J. A.; Melzer-Gartzke, C.; Francis, Roland C. E. (Acta Anaesthesiologica Scandinavica, 2018)
CRIS-Team Scopus Importer:2022-11-17

Routine frailty assessment predicts postoperative complications in elderly patients across surgical disciplines - A retrospective observational study - Birkelbach, Oliver; Moergeli, Rudolf; Spies, Claudia; Olbert, Maria; Weiss, Bjoern; Brauner, Maximilian; Neuner, Bruno; Francis, Roland C. E.; Treskatsch, Sascha; Balzer, Felix (BMC Anesthesiology, 2019)
Background: Frailty is a frequent and underdiagnosed functional syndrome involving reduced physiological reserves and an increased vulnerability against stressors, with severe individual and socioeconomic consequences. A routine frailty assessment was implemented at our preoperative anaesthesia clinic to identify patients at risk. Objective: This study examines the relationship between frailty status and the incidence of in-hospital postoperative complications in elderly surgical patients across several surgical disciplines. Design: Retrospective observational analysis. Setting: Single center, major tertiary care university hospital. Data collection took place between June 2016 and March 2017. Patients: Patients 65 years old or older were evaluated for frailty using Fried's 5-point frailty assessment prior to elective non-cardiac surgery. Patients were classified into non-frail (0 criteria, reference group), pre-frail (1-2 positive criteria) and frail (3-5 positive criteria) groups. Main outcome measures: The incidence of postoperative complications was assessed until discharge from the hospital, using the roster from the National VA Surgical Quality Improvement Program. Propensity score matching and logistic regression analysis were performed. Results: From 1186 elderly patients, 46.9% were classified as pre-frail (n = 556), and 11.4% as frail (n = 135). The rate of complications were significantly higher in the pre-frail (34.7%) and frail groups (47.4%), as compared to the non-frail group (27.5%). Similarly, length of stay (non-frail: 5.0 [3.0;7.0], pre-frail: 7.0 [3.0;9.0], frail 8.0 [4.5;12.0]; p < 0.001) and discharges to care facilities (non-frail:1.6%, pre-frail: 7.4%, frail: 17.8%); p < 0.001) were significantly associated with frailty status. After propensity score matching and logistic regression analysis, the risk for developing postoperative complications was approximately two-fold for pre-frail (OR 1.78; 95% CI 1.04-3.05) and frail (OR 2.08; 95% CI 1.21-3.60) patients. Conclusions: The preoperative frailty assessment of elderly patients identified pre-frail and frail subgroups to have the highest rate of postoperative complications, regardless of age, surgical discipline, and surgical risk. Significantly increased length of hospitalisation and discharges to care facilities were also observed. Implementation of routine frailty assessments appear to be an effective tool in identifying patients with increased risk. Now future studies are needed to investigate whether patients benefit from optimization of patient counselling, process planning, and risk reduction protocols based on the application of risk stratification.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Elderly; Frailty; Outcome; Perioperative

Safe pediatric anesthesia - From evidence to practice! Sichere Kinderanästhesie - von der Evidenz zur Praxis! - Francis, Roland C. E.; Spies, Claudia (AINS - Anästhesiologie. Intensivmedizin. Notfallmedizin. Schmerztherapie., 2018)
CRIS-Team Scopus Importer:2022-11-17

Slow releasing sulphide donor GYY4137 protects mice against ventilator-induced lung injury - Veskemaa, Lilly; Taher, Mahdi; Graw, Jan Adriaan; Gonzalez-Lopez, Adrian; Francis, Roland (Intensive Care Medicine Experimental, 2025)
Background: Cyclic stretching of the lung during mechanical ventilation induces inflammation that contributes to the development of ventilator induced lung injury. Hydrogen sulphide (H2S) is an endogenous gasotransmitter known for its anti-inflammatory properties. However, the administration of exogenous H2S is constrained by its narrow therapeutic window, rapidly leading to potentially toxic peak concentrations. Alternatively, slow-release sulphide donors, such as GYY4137, offer a more controlled delivery. The primary aim of this study is to assess the efficacy and safety of GYY4137 in mitigating VILI. Methods: Anaesthetised male C57BL/6 J mice were pretreated with an intraperitoneal injection of GYY4137 (50 mg/kg, n = 14) or an equivalent volume of phosphate-buffered saline (controls, n = 13) and were then subjected to high tidal volume ventilation (VT 40–42.5 ml/kg) for a maximum of 4 h. Results: GYY4137 pretreatment led to a notable 50% increase in survival rates compared to controls (p = 0.0025). It also improved arterial oxygenation after high VT ventilation, with arterial partial pressure of oxygen (PaO2) of 64 mmHg (IQR 49–125 mmHg) vs. 44 mmHg (IQR 42–51 mmHg) in controls (p < 0.001). Additionally, GYY4137 reduced total protein concentration in bronchoalveolar lavage fluid by 30% (p = 0.024) and lowered IL-1β levels by 40% (p = 0.006). GYY4137 mitigated the decline in dynamic respiratory system compliance caused by high VT ventilation, showing values of 24 μl/cmH2O (IQR 22–27) compared to 22 μl/cmH2O (IQR 22–24) in controls (p = 0.017). GYY4137 had minimal effects on antioxidant gene expression related to the erythroid nuclear factor 2, and it did not affect glutathione metabolism, the nuclear factor kappa B pathway, or the endoplasmic reticulum stress response. Conclusions: In this mouse model of VILI, pretreatment with GYY4137 showed protective effects. GYY4137 significantly improved survival. It also improved arterial blood oxygenation and dynamic respiratory system compliance, and mitigated the development of lung oedema and inflammation.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Biotrauma; Hydrogen sulphide; Sulphide donors; Ventilator-induced lung injury

Sodium nitrite mitigates ventilator-induced lung injury in rats - Pickerodt, Philipp A.; Emery, Michael J.; Zarndt, Rachel; Martin, William; Francis, Roland C. E.; Boemke, Willehad; Swenson, Erik R. (Anesthesiology, 2012)
BACKGROUND:: Nitrite (NO2) is a physiologic source of nitric oxide and protects against ischemia-reperfusion injuries. We hypothesized that nitrite would be protective in a rat model of ventilator-induced lung injury and sought to determine if nitrite protection is mediated by enzymic catalytic reduction to nitric oxide. METHODS:: Rats were anesthetized and mechanically ventilated. Group 1 had low tidal volume ventilation (LVT) (6 ml/kg and 2 cm H2O positive end-expiratory pressure; n = 10); group 2 had high tidal volume ventilation (HVT) (2 h of 35 cm H2O inspiratory peak pressure and 0 cm H2O positive end-expiratory pressure; n = 14); groups 3-5: HVT with sodium nitrite (NaNO2) pretreatment (0.25, 2.5, 25 μmol/kg IV; n = 6-8); group 6: HVT + NaNO2 + nitric oxide scavenger 2-(4-carboxyphenyl)-4,5dihydro-4,4,5,5-tetramethyl-1H- imidazolyl-1-oxy-3oxide(n = 6); group 7: HVT + NaNO2 + nitric oxide synthase inhibitor N-nitro-L-arginine methyl ester (n = 7); and group 8: HVT + NaNO2 + xanthine oxidoreductase inhibitor allopurinol (n = 6). Injury assessment included physiologic measurements (gas exchange, lung compliance, lung edema formation, vascular perfusion pressures) with histologic and biochemical correlates of lung injury and protection. RESULTS:: Injurious ventilation caused statistically significant injury in untreated animals. NaNO2 pretreatment mitigated the gas exchange deterioration, lung edema formation, and histologic injury with maximal protection at 2.5 μmol/kg. Decreasing nitric oxide bioavailability by nitric oxide scavenging, nitric oxide synthase inhibition, or xanthine oxidoreductase inhibition abolished the protection by NaNO2. CONCLUSIONS:: Nitrite confers protection against ventilator-induced lung injury in rats. Catalytic reduction to nitric oxide and mitigation of ventilator-induced lung injury is dependent on both xanthine oxidoreductase and nitric oxide synthases. Copyright © 2012, the American Society of Anesthesiologists, Inc. Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2022-11-17

Sodium Thiosulfate Reduces Acute Kidney Injury in Patients Undergoing Cytoreductive Surgery Plus Hyperthermic Intraperitoneal Chemotherapy with Cisplatin: A Single-Center Observational Study - Kurreck, Annika; Gronau, Felix; Vilchez, Miguel Enrique Alberto; Abels, Wiltrud; Enghard, Philipp; Brandl, Andreas; Francis, Roland C. E.; Foehre, Bettina; Lojewski, Christian; Pratschke, Johann; Thuss-Patience, Peter; Modest, Dominik; et al. (Annals of Surgical Oncology, 2022)
Background: Cytoreductive surgery (CRS) in combination with hyperthermic intraperitoneal chemotherapy (HIPEC) represents a multimodal treatment concept for patients with peritoneal surface malignancies. The use of intraperitoneal cisplatin (CDDP) is associated with a risk of acute kidney injury (AKI). The aim of this study is to evaluate the protective effect of perioperative sodium thiosulfate (STS) administration on kidney function in patients undergoing CRS and CDDP-based HIPEC. Patients and Methods: We retrospectively analyzed clinical data of all patients who underwent CRS and CDDP-based HIPEC at our hospital between March 2017 and August 2020. Patients were stratified according to the use of sodium thiosulfate (STS vs. no STS). We compared kidney function and clinical outcome parameters between both groups and determined risk factors for postoperative AKI on univariate and multivariate analysis. AKI was classified according to acute kidney injury network (AKIN) criteria. Results: Of 238 patients who underwent CRS and CDDP-based HIPEC, 46 patients received STS and 192 patients did not. There were no significant differences in baseline characteristics. In patients who received STS, a lower incidence (6.5% vs. 30.7%; p = 0.001) and severity of AKI (p = 0.009) were observed. On multivariate analysis, the use of STS (OR 0.089, p = 0.001) remained an independent kidney-protective factor, while arterial hypertension (OR 5.283, p < 0.001) and elevated preoperative urea serum level (OR 5.278, p = 0.032) were predictors for postoperative AKI. Conclusions: The present data suggest that STS protects patients from AKI caused by CRS and CDDP-based HIPEC. Further prospective studies are needed to validate the benefit of STS among kidney-protective strategies.
CRIS-Team Scopus Importer:2022-11-17

SOLVe: a closed-loop system focused on protective mechanical ventilation - von Platen, Philip; Pickerodt, Philipp A.; Russ, Martin; Taher, Mahdi; Hinken, Lea; Braun, Wolfgang; Köbrich, Rainer; Pomprapa, Anake; Francis, Roland C. E.; Leonhardt, Steffen; Walter, Marian (Biomedical Engineering Online, 2023)
BACKGROUND: Mechanical ventilation is an essential component in the treatment of patients with acute respiratory distress syndrome. Prompt adaptation of the settings of a ventilator to the variable needs of patients is essential to ensure personalised and protective ventilation. Still, it is challenging and time-consuming for the therapist at the bedside. In addition, general implementation barriers hinder the timely incorporation of new evidence from clinical studies into routine clinical practice. RESULTS: We present a system combing clinical evidence and expert knowledge within a physiological closed-loop control structure for mechanical ventilation. The system includes multiple controllers to support adequate gas exchange while adhering to multiple evidence-based components of lung protective ventilation. We performed a pilot study on three animals with an induced ARDS. The system achieved a time-in-target of over 75 % for all targets and avoided any critical phases of low oxygen saturation, despite provoked disturbances such as disconnections from the ventilator and positional changes of the subject. CONCLUSIONS: The presented system can provide personalised and lung-protective ventilation and reduce clinician workload in clinical practice.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Acute respiratory distress syndrome; Physiological closed-loop control; Protective ventilation

Standardized High-Quality Processes for End-of-Life-Decision Making in the Intensive Care Unit Remain Robust during an Unprecedented New Pandemic—A Single-Center Experience - Marsch, Fanny; Spies, Claudia D.; Francis, Roland; Graw, Jan A. (International Journal of Environmental Research and Public Health, 2022)
Due to the global COVID-19 pandemic, a concomitant increase in awareness for end-of-life decisions (EOLDs) and advance care planning has been noted. Whether the dynamic pandemic situation impacted EOLD-processes on the intensive care unit (ICU) and patient-sided advance care planning in Germany is unknown. This is a retrospective analysis of all deceased patients of surgical ICUs of a university medical center from March 2020 to July 2021. All included ICUs had established standardized protocols and documentation for EOLD-related aspects of ICU therapy. The frequency of EOLDs and advance directives and the process of EOLDs were analyzed (No. of ethical approval EA2/308/20). A total number of 319 (85.5%) of all deceased patients received an EOLD. Advance directives were possessed by 83 (22.3%) of the patients and a precautionary power of attorney by 92 (24.7%) of the patients. There was no difference in the frequency of EOLDs and patient-sided advance care planning between patients with COVID-19 and non-COVID-19 patients. In addition, no differences in frequencies of do-not-resuscitate orders, withholding or withdrawing of intensive care medicine therapeutic approaches, timing of EOLDs, and participation of senior ICU attendings in EOLDs were noted between patients with COVID-19 and non-COVID-19 patients. Documentation of family conferences occurred more often in deceased patients with COVID-19 compared to non-COVID-19 patients (COVID-19: 80.0% vs. non-COVID-19: 56.8, p = 0.001). Frequency of EOLDs and completion rates of advance directives remained unchanged during the pandemic compared to pre-pandemic years. The EOLD process did not differ between patients with COVID-19 and non-COVID-19 patients. Institutional standard procedures might contribute to support the robustness of EOLD-making processes during unprecedented medical emergencies, such as new pandemic diseases.
CRIS-Team Scopus Importer:2022-12-02
Keywords: advance directive; COVID-19; end-of-life decision; intensive care unit; shared decision making

Standard operating procedures as a tool to improve medical documentation in preclinical emergency medicine. - Francis, Roland C. E.; Schmidbauer, Willi; Spies, Claudia D.; Soerensen, Marc; Bubser, Florian; Kerner, Thoralf (Emergency Medicine Journal, 2010)
To evaluate the effect of standard operating procedures (SOPs) to improve the completion of patient care documentation items on patient care reports (PCRs) in a physician-staffed, 4500-calls-per-year preclinical ground emergency medical service (EMS) base. Two series of PCRs were analysed before (n=505) and after (n=520) the introduction of SOPs. PCR forms were analysed for the rate of completion of documentation comparing prompted data in check boxes and non-prompted data written in blank spaces at the discretion of the emergency physician. The chi2 test for independence was used to assess the effect of SOPs and prompting on data completion rate. SOPs improved the documentation rate of numerous prompted and non-prompted items, independent of whether these items had a high (eg, Glasgow Coma Score: 91.5% vs 95.7%) or a low documentation rate during the pre-SOP period (eg, allergies: 6.2% vs 18.7%). Prompted items were more frequently documented than non-prompted items, both before and after the introduction of SOPs. Lowest rates were found among non-prompted items (eg, 'last meal' 3.6%). In this EMS base, developing SOPs is an effective tool to improve the quality of PCRs and the rate of completion of documentation items. Check boxes on PCR forms seem to have an important impact as they prompt the initial assessment, treatment and documentation of the actions taken during an EMS call. Consequently, SOPs and check boxes may serve to improve the transition of important information to emergency department staff, and thus contribute to improved patient care.
CRIS-Team Scopus Importer:2022-11-17

Surfactant depletion combined with injurious ventilation results in a reproducible model of the acute respiratory distress syndrome (Ards) - Russ, Martin; Boerger, Emilia; Von Platen, Philip; Francis, Roland C. E.; Taher, Mahdi; Boemke, Willehad; Lachmann, Burkhard; Leonhardt, Steffen; Pickerodt, Philipp A. (Journal of Visualized Experiments, 2021)
Various animal models exist to study the complex pathomechanisms of the acute respiratory distress syndrome (ARDS). These models include pulmo-arterial infusion of oleic acid, infusion of endotoxins or bacteria, cecal ligation and puncture, various pneumonia models, lung ischemia/reperfusion models and, of course, surfactant depletion models, among others. Surfactant depletion produces a rapid, reproducible deterioration of pulmonary gas exchange and hemodynamics and can be induced in anesthetized pigs using repeated lung lavages with 0.9% saline (35 mL/kg body weight, 37 °C). The surfactant depletion model supports investigations with standard respiratory and hemodynamic monitoring with clinically applied devices. But the model suffers from a relatively high recruitability and ventilation with high airway pressures can immediately reduce the severity of the injury by reopening atelectatic lung areas. Thus, this model is not suitable for investigations of ventilator regimes that use high airway pressures. A combination of surfactant depletion and injurious ventilation with high tidal volume/low positive end-expiratory pressure (high Tv/low PEEP) to cause ventilator induced lung injury (VILI) will reduce the recruitability of the resulting lung injury. The advantages of a timely induction and the possibility to perform experimental research in a setting comparable to an intensive care unit are preserved.
CRIS-Team Scopus Importer:2022-11-17

Tert-butylhydroquinone augments Nrf2-dependent resilience against oxidative stress and improves survival of ventilator-induced lung injury in mice - Veskemaa, Lilly; Graw, Jan A.; Pickerodt, Philipp A.; Taher, Mahdi; Boemke, Willehad; Gonzalez-Lopez, Adrian; Francis, Roland C. E. (American Journal of Physiology-Lung Cellular and Molecular Physiology, 2021)
Oxidative stress caused by mechanical ventilation contributes to the pathophysiology of ventilator-induced lung injury (VILI). A key mechanism maintaining redox balance is the upregulation of nuclear factor-erythroid-2-related factor 2 (Nrf2)-dependent antioxidant gene expression. We tested whether pretreatment with an Nrf2-antioxidant response element (ARE) pathway activator tert-butylhydroquinone (tBHQ) protects against VILI. Male C57BL/6J mice were pretreated with an intraperitoneal injection of tBHQ (n = 10), an equivalent volume of 3% ethanol (EtOH3%, vehicle, n = 13), or phosphate-buffered saline (controls, n = 10) and were then subjected to high tidal volume (HVT) ventilation for a maximum of 4 h. HVT ventilation severely impaired arterial oxygenation (PaO2 = 49 ± 7 mmHg, means ± SD) and respiratory system compliance, resulting in a 100% mortality among controls. Compared with controls, tBHQ improved arterial oxygenation (PaO2 = 90 ± 41 mmHg) and respiratory system compliance after HVT ventilation. In addition, tBHQ attenuated the HVT ventilation-induced development of lung edema and proinflammatory response, evidenced by lower concentrations of protein and proinflammatory cytokines (IL-1b and TNF-a) in the bronchoalveolar lavage fluid, respectively. Moreover, tBHQ enhanced the pulmonary redox capacity, indicated by enhanced Nrf2-depentent gene expression at baseline and by the highest total glutathione concentration after HVT ventilation among all groups. Overall, tBHQ pretreatment resulted in 60% survival (P < 0.001 vs. controls). Interestingly, compared with controls, EtOH3% reduced the proinflammatory response to HVT ventilation in the lung, resulting in 38.5% survival (P = 0.0054 vs. controls). In this murine model of VILI, tBHQ increases the pulmonary redox capacity by activating the Nrf2-ARE pathway and protects against VILI. These findings support the efficacy of pharmacological Nrf2-ARE pathway activation to increase resilience against oxidative stress during injurious mechanical ventilation.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Lung; Redox; TBHQ; Ventilation; VILI

The Relevance of Hemolysis in Anesthesia and Intensive Care Medicine Die Bedeutung der Hämolyse in Anästhesie und Intensivmedizin - Graw, Jan A.; Baron, David M.; Francis, Roland C. E. (AINS - Anästhesiologie. Intensivmedizin. Notfallmedizin. Schmerztherapie., 2018)
Hemolysis leads to an increase of circulating intravascular cell-free hemoglobin. Increased plasma concentrations of cell-free hemoglobin are relevant in critically ill patients because cell-free hemoglobin causes vasoconstriction by depletion of endothelial nitric oxide, oxidative stress, and inflammation. Furthermore, cell-free hemoglobin contributes to tissue injuries such as renal failure and intestinal mucosa damage after cardiac surgery. High concentrations of cell-free hemoglobin are associated with an increased mortality in patients with sepsis. Currently, it is unclear if hemolysis associated with transfusion of packed red blood cells that have been stored for prolonged periods of time is relevant for the clinical outcome. However, humans possess plasma proteins haptoglobin and hemopexin which bind to plasma hemoglobin and cell-free heme, respectively. The haptoglobin-hemoglobin and hemopexin-heme complexes are then eliminated from the plasma by hepatic or splenic uptake.
CRIS-Team Scopus Importer:2022-11-17
Keywords: blood transfusion; cell-free hemoglobin; haptoglobin; heme; hemolysis

The role of cell-free hemoglobin and haptoglobin in acute kidney injury in critically ill adults with ARDS and therapy with VV ECMO - Graw, Jan A.; Hildebrandt, Philip; Krannich, Alexander; Balzer, Felix; Spies, Claudia; Francis, Roland C. E.; Kuebler, Wolfgang M.; Weber-Carstens, Steffen; Menk, Mario; Hunsicker, Oliver (Critical Care, 2022)
Background: Increased plasma concentrations of circulating cell-free hemoglobin (CFH) are supposed to contribute to the multifactorial etiology of acute kidney injury (AKI) in critically ill patients while the CFH-scavenger haptoglobin might play a protective role. We evaluated the association of CFH and haptoglobin with AKI in patients with an acute respiratory distress syndrome (ARDS) requiring therapy with VV ECMO. Methods: Patients with CFH and haptoglobin measurements before initiation of ECMO therapy were identified from a cohort of 1044 ARDS patients and grouped into three CFH concentration groups using a risk stratification. The primary objective was to assess the association of CFH and haptoglobin with KDIGO stage 3 AKI. Further objectives included the identification of a target haptoglobin concentration to protect from CFH-associated AKI. Measurements and main results: Two hundred seventy-three patients fulfilled the inclusion criteria. Of those, 154 patients (56.4%) had AKI at ECMO initiation. The incidence of AKI increased stepwise with increasing concentrations of CFH reaching a plateau at 15 mg/dl. Compared to patients with low [< 5 mg/dl] CFH concentrations, patients with moderate [5–14 mg/dl] and high [≥ 15 mg/dl] CFH concentrations had a three- and five-fold increased risk for AKI (adjusted odds ratio [OR] moderate vs. low, 2.69 [95% CI, 1.25–5.95], P = 0.012; and OR high vs. low, 5.47 [2.00–15.9], P = 0.001). Among patients with increased CFH concentrations, haptoglobin plasma levels were lower in patients with AKI compared to patients without AKI. A haptoglobin concentration greater than 2.7 g/l in the moderate and 2.4 g/l in the high CFH group was identified as clinical cutoff value to protect from CFH-associated AKI (sensitivity 89.5% [95% CI, 83–96] and 90.2% [80–97], respectively). Conclusions: In critically ill patients with ARDS requiring therapy with VV ECMO, an increased plasma concentration of CFH was identified as independent risk factor for AKI. Among patients with increased CFH concentrations, higher plasma haptoglobin concentrations might protect from CFH-associated AKI and should be subject of future research.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Acute kidney injury; ARDS; Cell-free hemoglobin; Haptoglobin

To measure is to know - But know what you measure - Spieth, P. M.; Francis, Roland C. E. (Minerva Anestesiologica, 2014)
CRIS-Team Scopus Importer:2022-11-17

Xenon/remifentanil anesthesia protects against adverse effects of losartan on hemodynamic challenges induced by anesthesia and acute blood loss - Francis, Roland C. E.; Philippi-Hoehne, Claudia; Klein, Adrian; Pickerodt, Philipp A.; Reyle-Hahn, Matthias S.; Boemke, Willehad (Shock, 2010)
The authors aimed to test the hypothesis that xenon anesthesia limits adverse hypotensive effects of losartan during acute hemorrhage. In six conscious unsedated Beagle dogs, the systemic and pulmonary circulation were monitored invasively, and two subsequent 60-min hypotensive challenges were performed by (a) induction (propofol) and maintenance of anesthesia with isoflurane/remifentanil or xenon/remifentanil and by (b) subsequent hemorrhage (20 mL kg-1 within 5 min) from a central vein. The same amount of blood was retransfused 1 h after hemorrhage. Experiments were performed with or without acute angiotensin II receptor subtype 1 blockade by i.v. losartan (100 μg·kg-1·min-1) starting 45 min before induction of anesthesia. Four experiments were performed in each individual dog. Xenon/remifentanil anesthesia provided higher baseline mean arterial blood pressure (85 ± 6 mmHg) than isoflurane/remifentanil anesthesia (67 ± 3 mmHg). In losartan-treated animals, isoflurane/remifentanil caused significant hypotension (42 ± 4 mmHg for isoflurane/remifentanil vs. 71 ± 6 mmHg for xenon/remifentanil). Independent of losartan, hemorrhage did not induce any further reduction of mean arterial blood pressure or cardiac output in either group. Spontaneous hemodynamic recovery was observed in all groups before retransfusion was started. Losartan did not alter the adrenaline, noradrenaline, and vasopressin response to acute hemorrhage. Losartan potentiates hypotension induced by isoflurane/remifentanil anesthesia but does not affect the hemodynamic stability during xenon/remifentanil anesthesia. Losartan does not deteriorate the hemodynamic adaptation to hemorrhage of 20 mL kg-1 during xenon/remifentanil and isoflurane/remifentanil anesthesia. Therefore, xenon/remifentanil anesthesia protects against circulatory side effects of losartan pretreatment and thus may afford safer therapeutic use of losartan during acute hemorrhage. Copyright © 2010 by the Shock Society.
CRIS-Team Scopus Importer:2022-11-17
Keywords: angiotensin II receptor antagonist; Hemorrhage; hypotension; isoflurane